Sustainable development and environmental restoration in Lake Erhai, China. (10th June 2020) - Lin, Song-Shun; Shen, Shui-Long; Zhou, Annan; Lyu, Hai-Min
Abstract: Eutrophication of lakes is an environmental issue that has attracted increasing attention all over the world. This study analyses the monitoring data of the Lake Erhai, Yunnan Province in China with Carlson's TSI, Improving Carlson's TSI (TSIM ) and TLI. The results reveal that the eutrophication index for this lake is in the Mesotrophic status. The mechanism of the eutrophication in Lake Erhai is also investigated. The mechanism shows that rate of nutrient transformation is the core issue and the process of eutrophic evolution involves natural, social, and economic factors. The restrictions on sustainable development in Lake Erhai are discussed. To maintain sustainable development, green watershed construction (GWC) and its corresponding effective measures are proposed. Moreover, lessons learned from Lake Erhai watershed management are presented, to provide valuable experiences for alleviating water pollution caused by insufficient environmental management during rapid economic development. Perspective future research works are proposed, including establishment of the early warning system with remote sensing (RS) and geographic information system (GIS) as well as the artificial intelligence (AI) technology. Highlights: Three trophic status indexes, e.g. TSI, TSIM, and TLI, are adopted to evaluate the water quality. We analysed causes of three severe outbreaks of blooms and impacts of eutrophication in Lake Erhai. Mechanism of eutrophication and restrictions to sustainability of Lake Erhai are demonstrated. Effective measures to maintain the sustainable development in watershed are provided. A successful experience of water treatment and management in Lake Erhai is demonstrated.